Exploration of The Meaning of Social Support on Psychological Well-Being Based on a Qualitative Phenomenological Study - Endin Nasrudin; Dadang Sahroni; Aeni Latifah (Westscience Press, 2026)
Psychological well-being is an important aspect of human life related to individuals’ ability to accept themselves, build positive relationships, establish life purposes, and cope adaptively with various challenges. In social life, psychological well-being is influenced by several factors, one of which is social support obtained from family, friends, and the surrounding environment. Social support functions as a source of emotional strength that helps individuals reduce stress, enhance self-confidence, and foster feelings of safety and appreciation. However, the meaning of social support may vary among individuals depending on their life experiences. This study aims to explore the meaning of social support on psychological well-being based on individuals’ subjective experiences. This research employed a qualitative approach using a phenomenological method to gain an in-depth understanding of participants’ lived experiences. Data were collected through in-depth interviews with purposively selected participants based on their experiences in receiving social support. Data analysis was conducted through data reduction, data display, and conclusion drawing, focusing on emerging experiential themes. The findings indicate that social support is interpreted as emotional care, tangible assistance, motivation, and the presence of others who provide comfort and security. Social support contributes to psychological well-being by fostering feelings of appreciation, increasing self-confidence, reducing psychological distress, and strengthening individuals’ capacity to cope with life challenges.